2022
DOI: 10.1007/s11356-022-20394-9
|View full text |Cite
|
Sign up to set email alerts
|

Re-examining the nexuses of communicable diseases, environmental performance, and dynamics of sustainable Development in OECD countries

Abstract: We investigate the determinants of communicable diseases (CDs) and nexus of financial development, economic development, and renewable energy consumption to address the issues of ecological footprint level, the impacts of communicable diseases (CDs), and economic growth of the OECD countries throughout 2000-2019. The results from FMOLS and DOLS reveal that the levels of financial development, energy consumption, and trade volume significantly contribute to overcoming the death toll occurring due to CDs. As reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Sureeyatanapas et al [38] stated that green logistics has a lot of room for improvement. Yu et al [39] applied a fuzzy mathematical model to model green logistics, which aims to improve the performance of green logistics and minimize logistic costs. Hajipour et al [40] suggested optimizing the location of logistics warehouses to decrease air pollution while reducing transportation costs.…”
Section: Green Logisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sureeyatanapas et al [38] stated that green logistics has a lot of room for improvement. Yu et al [39] applied a fuzzy mathematical model to model green logistics, which aims to improve the performance of green logistics and minimize logistic costs. Hajipour et al [40] suggested optimizing the location of logistics warehouses to decrease air pollution while reducing transportation costs.…”
Section: Green Logisticsmentioning
confidence: 99%
“…Reference Industrial performance [9,20,28,46] Profit [11,17,31,32,[39][40][41]54,56,59,67] Eco-design [12,16,17,20,21,22,24,25,55] Product brand [13] Optimization modeling [18,30,33,[38][39][40][41]43,46,48 Tao et al [60] modeled the remanufacturing process by using price, technical, and material parameters. Dong et al [61] analyzed the economic factors of products returned by consumers at distribution agents.…”
Section: Gscm Parametermentioning
confidence: 99%